Digital Islamic Finance In Indonesia: Challenges and Opportunities From A Public Policy Perspective - Houria Ben Gharbi (Universitas Ahmad Dahlan, 2025)
Introduction to The Problem: Digital Islamic finance is increasingly recognized as a strategic tool for promoting inclusive, ethical, and sustainable financial systems worldwide. In Indonesia, as the largest Muslim-majority country, Shariah-compliant digital finance plays a central role in national agendas for financial inclusion and sustainable economic development. Purpose/Objective Study: This study aims to examine the progress and institutional dynamics shaping digital Islamic finance in Indonesia from a public policy perspective, focusing on regulatory frameworks and the roles of key national institutions. Design/Methodology/Approach: Employing a qualitative content analysis approach, this research analyzes relevant laws, policy documents, and institutional reports to identify major developments, governance structures, and implementation challenges within the sector. Findings: The findings reveal significant advancements, including the enactment of Law No. 4/2023, the Digital Sharia Banking Roadmap (RP3SI), and initiatives led by the Financial Services Authority (OJK) and the National Committee for Islamic Economy and Finance (KNEKS). These efforts have strengthened financial literacy, expanded green sukuk instruments, and supported inclusive digital finance pilot programs. However, persistent challenges remain, such as rural infrastructure disparities, limited integration between ESG and Shariah principles, and fragmented regulatory oversight, which collectively hinder broader societal impact.